The Influence Of Service Quality, Price, And Facilities On Customer Satisfaction At Jungle In And Restaurant In Supporting Tourism In Bukit Lawang Langkat, North Sumatra - Reza Kurniawan; Slamet Widodo (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
A restaurant is a business that offers food and beverages to customers to be consumed on-site or taken away. Basically, restaurants have a variety of menu options dedicated to specific themes, such as traditional, international, fast food, or fine dining. Restaurants are not just places to eat, but also places to relax, socialize, or even hold business meetings. Jungle in and restaurant is one of the businesses operating in this field. This restaurant is located by the river and has a lush forest surrounding it. This makes it different from other restaurants located in the city center or in crowded places. Jungle Inn and Restaurant is facing the problem of declining customers and fluctuating customer numbers every month. The impact of Service Quality, Price, and Facilities on Customer Satisfaction at Jungle Inn and Restaurant in Bukit Lawang Langkat, North Sumatra, is the subject of this research. data collection through the distribution of questionnaires to 95 respondents. The multiple linear regression model with SPSS processing was used in this study. The research results show that service quality partially has a positive and significant effect, price partially has a positive and significant effect, and facilities partially do not have a positive and significant effect. The Adjusted R Square value of 0.550 indicates that service quality, price, and facilities can contribute fifty-five percent (55%) to customer satisfaction, with the remaining forty-five percent (45%) potentially attributed to other unexamined variables.